A Comparative Interaction Of He-Ne And Co2 Laser Irradiation On Human Blood And Its Components - Houssein, Hend A A (2011)
In this study, the subpopulations of human blood parameters which consist of white blood cells, red blood cells, platelets, and its components were determined by electronic sizing in the Sejahtera Centre of Universiti Sains Malaysia. These parameters have been correlated with human characteristics such as age, gender, ethnicity, blood groups, body mass index, and various medical histories, before and after irradiation with 632.8 nm He-Ne laser at energy density of 1.7 x 10-17 J/cm2, and with 10,600 nm CO2 laser at energy density of 1.9 x 10-19 J/cm2. Correlations were obtained by finding patterns in changes of blood parameters using paired and independent tests and the relationships were identified by using regression analysis.